2008
DOI: 10.1073/pnas.0804636105
|View full text |Cite
|
Sign up to set email alerts
|

A photoactive carotenoid protein acting as light intensity sensor

Abstract: Intense sunlight is dangerous for photosynthetic organisms. Cyanobacteria, like plants, protect themselves from light-induced stress by dissipating excess absorbed energy as heat. Recently, it was discovered that a soluble orange carotenoid protein, the OCP, is essential for this photoprotective mechanism. Here we show that the OCP is also a member of the family of photoactive proteins; it is a unique example of a photoactive protein containing a carotenoid as the photoresponsive chromophore. Upon illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
436
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(463 citation statements)
references
References 35 publications
25
436
2
Order By: Relevance
“…OCP acts as a blue-green light intensity sensor (5). In vivo under strong light, OCP is converted to its active signaling state, which interacts with phycobilisomes and quenches the excess of excitation energy (3,(6)(7)(8)(9), thereby decreasing the effective absorption cross section of the photosystems and preventing the formation of potentially damaging reactive oxygen species (10).…”
Section: Introductionmentioning
confidence: 99%
“…OCP acts as a blue-green light intensity sensor (5). In vivo under strong light, OCP is converted to its active signaling state, which interacts with phycobilisomes and quenches the excess of excitation energy (3,(6)(7)(8)(9), thereby decreasing the effective absorption cross section of the photosystems and preventing the formation of potentially damaging reactive oxygen species (10).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, we demonstrated that a Synechocystis mutant lacking OCP (DOCP) was more sensitive to high intensities of white light than Synechocystis wild type (Wilson et al, 2008). Moreover, cyanobacterial strains lacking OCP were photoinhibited faster than strains containing OCP under fluctuating light conditions (Boulay et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Although this protein has been known since 1981 (Holt and Krogmann, 1981) and its structure was resolved in 2003 (Kerfeld et al, 2003), only in 2006 did researchers discover that OCP is essential for a photoprotective mechanism decreasing the energy arriving at the reaction centers (Wilson et al, 2006). OCP is a photoactive protein (Wilson et al, 2008) and the only photosensory protein described to date that has a carotenoid as the active chromophore. Absorption of blue-green light by the carotenoid induces conformational changes in both the carotenoid and the protein, changes that are essential for its function in the photoprotective mechanism (Wilson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations